Tumour necrosis factor‐α plus interleukin‐10 low producer phenotype predicts acute kidney injury and death in intensive care unit patients. (4th July 2013) - Dalboni, M. A.; Quinto, B. M. R.; Grabulosa, C. C.; Narciso, R.; Monte, J. C.; Durão, M.; Rizzo, L.; Cendoroglo, M.; Santos, O. P.; Batista, M. C.
Summary Genetic polymorphism studies of cytokines may provide an insight into the understanding of acute kidney injury (AKI) and death in intensive care unit (ICU) patients. The aim of this study was to investigate whether the genetic polymorphisms of −308 G < A tumour necrosis factor (TNF)‐α, −174 G > C interleukin (IL)‐6 and −1082 G > A IL‐10 may predispose ICU patients to the development of AKI and/or death. In a prospective nested case–control study, 303 ICU patients and 244 healthy individuals were evaluated. The study group included ICU patients who developed AKI (n = 139) and 164 ICU patients without AKI. The GG genotype of TNF‐α (low producer phenotype) was significantly lower in the with AKI than without AKI groups and healthy individuals (55 versus 62 versus 73%, respectively; P = 0·01). When genotypes were stratified into four categories of TNF‐α/IL‐10 combinations, it was observed that low TNF‐α plus low IL‐10 producer phenotypes were more prevalent in patients with AKI, renal replacement therapy and death (P < 0·05). In logistic regression analysis, low TNF‐α producer plus low IL‐10 producer phenotypes remained as independent risk factors for AKI and/or death [odds ratio (OR) = 2·37, 95% confidence interval (CI): 1·16–4·84; P = 0·02] and for renal replacement therapy (RRT) and/or death (OR = 3·82, 95% CI: 1·19–12·23; P = 0·02). In this study, the combination of low TNF‐α plus low IL‐10 producer phenotypes was an independent risk factor to AKI and/or death and RRT and/or death in critically ill patients. Our results should be validated in a larger prospective study with long‐term follow‐up to emphasize the combination of these genotypes as potential risk factors to AKI in critically ill patients.